PENGGUNAAN MEDIA AUDIO VISUAL MELALUI PEMBELAJARAN MENDALAM (DEEP LEARNING) DALAM MENULIS TEKS PROSEDUR FASE D SMP NEGERI 34 MUARO JAMBI - Safrina; Rahmawati, Sophia; Mukhoiyaroh Bambang, Siti Enik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article, titled "The Use of Audio-Visual Media through Deep Learning in Writing Procedure Texts for Phase D Students at SMP Negeri 34 Muaro Jambi," aims to describe the use of audio-visual media via deep learning in procedure text writing instruction and to assess its effectiveness among Phase D students at SMP Negeri 34 Muaro Jambi. The study employs a qualitative approach using a case study design. The research subjects were seventh-grade students at SMP Negeri 34 Muaro Jambi. Data collection involved observation, interviews, and documentation, while data analysis comprised data reduction, data presentation, and conclusion drawing. The results indicate that the use of audio-visual media through deep learning was implemented in three stages: understanding, applying, and reflecting. In the understanding stage, students observed videos and identified the elements of procedure texts. In the applying stage, students drafted procedure texts individually based on the understanding they had gained. In the reflecting stage, students and the teacher engaged in reflection and received feedback on the written work. The use of audio-visual media through deep learning proved effective, evidenced by an average student score of 85, classified as "excellent." Furthermore, interview results revealed positive responses from both teachers and students, as the method enhanced attention, engagement, comprehension, and students' ability to write procedure texts. Thus, the use of audio-visual media through deep learning is effective for teaching procedure text writing to Phase D students at SMP Negeri 34 Muaro Jambi.